Epidemiological analysis of the victıms wıth crush syndrome in earthquakes of southeastern Turkey - Ozturk, Ilyas; Gungor, Ozkan; Ozturk, Savas; Olmaz, Refik; Keskin, Ayse Jini Gunes; Kocyigit, Ismail; Sever, Mehmet Sukru (Springer Heidelberg, 2024)
BackgroundEach year, millions face natural disasters, encountering mass fatalities and severe medical issues such as crush injuries and crush syndrome. Crush syndrome, marked by acute kidney injury (AKI) and hyperkalemia, correlates with mortality. This study focuses on presenting epidemiological data on kidney disease resulting from the February 6, 2023 earthquakes centered in Kahramanmaras.MethodsThis retrospective analysis included patients diagnosed with crush syndrome after the 2023 Kahramanmaras earthquakes, treated in regional hospitals or referred elsewhere in Turkey. Patient data were documented using the web-based system developed by the Turkish Nephrology Association Renal Disaster Working Group.ResultsOf the 1024 analyzed patients from 46 centers, 515 (50.3%) were women. The mean age was 41 +/- 16 years, with a median duration of 12 h under rubble, and the median presentation time to the first health facility was 4 h after extrication from the rubble. Upon admission, 79.8% received intravenous fluid therapy, all potassium-free. Initial serum creatinine, K+, and creatinine kinase levels averaged 2.59 +/- 2 mg/dl, 5.1 +/- 1 mmol/L 38,305 +/- 54,303 U/L, respectively. Intensive care unit (ICU) admissions were 53.6%, with mean hospital and ICU stays of 20 and 11 days, respectively. Compartment syndrome occurred in 40.8% of patients, with 75.8% undergoing fasciotomy. Acute kidney injury developed in 67.9% of patients, with 70.3% undergoing hemodialysis, totaling 3016 sessions on 488 patients. The overall in-hospital mortality rate was 9.8%.ConclusionEarthquakes have a significant impact on kidney health. Although our study indicates some progress compared to previous earthquake responses, there remains a crucial need for drills emphasizing post-earthquake initial response, fluid-electrolyte balance management, and emergency dialysis protocols.
Keywords: Crush syndrome; Disaster; Earthquake; Epidemiology